Allergen‐specific immunotherapy with apples: selected cultivars could be a promising tool for birch pollen allergy. (16th February 2020) - Nothegger, B.; Reider, N.; Covaciu, C.E.; Cova, V.; Ahammer, L.; Eidelpes, R.; Unterhauser, J.; Platzgummer, S.; Tollinger, M.; Letschka, T.; Eisendle, K.
Abstract: Background: Most birch pollen‐allergic patients develop allergic cross‐reactions to the major allergen found in apples Mal d1, known as pollen‐related food allergy (prFA). This is due to a strong clinically relevant homology between the major allergen in birch Bet v 1 and Mal d 1. Daily apple consumption induces oral tolerance in prFA, but its effect on the inhalational allergy has not been investigated. Objectives: As continuous apple consumption might also mitigate the inhalational allergy, this study aimed to uncover apple cultivars suitable for treatment of birch pollen rhinoconjunctivitis and apple allergy in a controlled and established dosage. Methods: Patients ( n  = 52) with birch pollen allergy and prFA to apples were subjected to a prick‐to‐prick test (SPT) with 23 cultivars (red‐fleshed, old traditional and new commercial). By SPT, the apple parts flesh, peel equatorial and peel apical near the stalk were compared for their reactivity. One apple cultivar of each allergenicity class (low, middle and high) was subsequently tested in an oral provocation test (OPT). Results: According to the SPTs, we provide a ranking of all 23 cultivars. Red‐fleshed apples displayed the lowest reactivity, followed by old and new cultivars. Four cultivars showed disagreement from their allergenicity class: Santana and Pink Lady®, new cultivars that provoked only low to moderate. In contrast, White Rosemary and Goldparmäne, two old cultivars, induced strong reactions. Skin reactivity increased from flesh to peel to stalk, and SPT results could predict the severity of prFA of each allergenicity class. Conclusions: Herein, we propose a treatment protocol for allergen immunotherapy to birch pollen and prFA with daily apple consumption. Red‐fleshed, old and the new cultivars Santana and Pink Lady® provoke less allergic reactions and are suitable for initial induction. After a controlled and well‐tolerated increase of intake, also moderate and finally high allergenic apple cultivars should be integrated into treatment of birch pollen allergenic patients. Abstract : Linked Commentary : K.‐C. Bergmann. J Eur Acad Dermatol Venereol 2020; 34: 1130–1130. https://doi.org/10.1111/jdv.16556 .